PERCEIVED VALUE SPECIAL ITEM SERIES DAN PURCHASED BEHAVIOR BS - LADY DI ERA DIGITAL TERHADAP FASHION LUXURY BRAND PADA PRODUK HIJAB BUTTONSCARVES - Ciptasari, Ayu Dita Windra; Pramesthi, Riska Ayu (Growth, 2024)
Indonesia is a country with a large population, where the majority of the population is Muslim. Indonesian people's interest in hijab fashion is increasing day by day along with the increasing interest of hijab designers in designing different and unique hijab motifs (Hidayanti et.al, 2018). Current developing trends mean that Indonesia also has a solid luxury fashion product ecosystem. The research methodology used by researchers in this study is a qualitative method. Qualitative methods are research to understand the phenomena experienced by research subjects, for example behavior, perception, motivation for action and so on. The aim of this research is to determine consumer behavior patterns in the digital era towards luxury brand fashion on hijab button scarves products. The research results show that there are several motives behind them buying luxury brands in Hijab Buttonscarves products, namely luxury brands are chosen because of the quality of the product and have selling value even as second hand goods or often referred to as preloved. In fact, there are 8 patterns of consumer behavior regarding Buttonscarves hijab products, namely: groups who make direct purchases in offline store for special item that’s only ready at offline store (Misool series and Switzerland), purchase directly item for all luxury series BS, purchase directly through the official Buttonscarves website or application, purchase through jastiper services, purchase through the marketplace or social media platforms, purchase through annual and group warehouse sales preloved hunter buyers. And purchase via blbli.com for special series champ de fleur. Apart from that, the influence of social media is quite large in searching for information about luxury brands, some consumers are comfortable buying or just browsing online.